The Effect of Accountability on the Efficiency of Local Government Expenditures - Wulan Sri Rahayu; Khoirunurrofik Khoirunurrofik (Badan Pemeriksa Keuangan Republik Indonesia, 2022)
This study aims to examine the effect of accountability, as one of the governance aspects, on the efficiency of local government spending at the district/city level in Indonesia. This study uses panel data analysis with 228 districts/city government entities from 2014 to 2018. The analysis is conducted in two stages; the first stage measures the efficiency of every local government by using Data Envelopment Analysis (DEA) method. The second stage estimates the effect of accountability and other control variables on local government expenditure efficiency by regression using the Tobit method. The result shows a non-linear relation between accountability, which is proxied using the Indonesia Audit Board Opinion Index, and the efficiency of local government expenditure. Initially, accountability will proceed hand in hand with increasing efficiency; however, at a certain point, an increase in accountability will no longer increase the efficiency level of local government expenditure. Another control variable that positively relates to efficiency is population expenditure per capita. Meanwhile, the ethnic fractionalization index (EFI) and distance negatively affect efficiency. The results of this study have not been able to show a relation between political competition and the gender of regional heads with efficiency.